PENGARUH ORIENTASI PASAR, BUDAYA ORGANISASI DAN ORIENTASI KEWIRAUSAHAAN TERHADAP KINERJA USAHA (Studi pada Usaha Kecil Pengolahan di Kota Palembang) - HERI SETIAWAN (Program Studi Magister Manajemen FE Unsri, 2013)
This study aimed to analyze the effect of Market Orientation, Organizational Culture and Entrepreneurial Orientation on the Marketing Performance of Small Businesses. The research was conducted by distributing questionnaires and interviews to the owner or manager of a small business in Palembang City. The population in this study is manufacturing of Small Business in Palembang, amount of 1,687. Based on the population obtained a sample of 94 respondents. Data collection techniques used is Disproportionate Stratified Random Sampling Method. Multiple Linear Regression Analysis was used to see the effect of the independent variables, namely Market Orientation, Organizational Culture and Orientation on Marketing Performance of Small Business. The results explained that the Market Orientation, Organizational Culture and Entrepreneurship Orientation simultaneously have significant effect on Marketing Performance OF Small Business. Then, partially market orientation have significant effect on Marketing Performance of Small Business. Organizational culture have significant effect on Marketing Performance OF Small Business. Entrepreneurship orientation have significant effect on Marketing Performance OF Small Business.